Assessing the relationship between psychosocial stressors and psychiatric resilience among Chilean disaster survivors. (November 2020) - Fernandez, Cristina A.; Choi, Karmel W.; Marshall, Brandon D. L.; Vicente, Benjamin; Saldivia, Sandra; Kohn, Robert; Koenen, Karestan C.; Arheart, Kristopher L.; Buka, Stephen L.
Abstract : Background: According to the stress inoculation hypothesis, successfully navigating life stressors may improve one's ability to cope with subsequent stressors, thereby increasing psychiatric resilience. Aims: Among individuals with no baseline history of post-traumatic stress disorder (PTSD) and/or major depressive disorder (MDD), to determine whether a history of a stressful life event protected participants against the development of PTSD and/or MDD after a natural disaster. Method: Analyses utilised data from a multiwave, prospective cohort study of adult Chilean primary care attendees (years 2003–2011; n = 1160). At baseline, participants completed the Composite International Diagnostic Interview (CIDI), a comprehensive psychiatric diagnostic instrument, and the List of Threatening Experiences, a 12-item questionnaire that measures major stressful life events. During the study (2010), the sixth most powerful earthquake on record struck Chile. One year later (2011), the CIDI was re-administered to assess post-disaster PTSD and/or MDD. Results: Marginal structural logistic regressions indicated that for every one-unit increase in the number of pre-disaster stressors, the odds of developing post-disaster PTSD or MDD increased (OR = 1.21, 95% CI 1.08–1.37, and OR = 1.16, 95% CI 1.06–1.27 respectively). When categorising pre-disaster stressors, individuals with four or more stressors (compared with no stressors) had higher odds of developing post-disaster PTSD (OR = 2.77, 95% CI 1.52–5.04), and a dose–response relationship between pre-disaster stressors and post-disaster MDD was found. Conclusions: In contrast to the stress inoculation hypothesis, results indicated that experiencing multiple stressors increased the vulnerability to developing PTSD and/or MDD after a natural disaster. Increased knowledge regarding the individual variations of these disorders is essential to inform targeted mental health interventions after a natural disaster, especially in under-studied populations.